2013
DOI: 10.1371/journal.pone.0059789
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Relatedness Predicts the Strength of Social Bonds among Female Rhesus Macaques

Abstract: Forming strong, equitable, and enduring social bonds with a few individuals in a group carries adaptive benefits in terms of increased longevity, offspring survival and paternity success in birds and mammals, including humans. These recent insights generated a new interest in the factors creating variation in the strength of social relationships. Whether and how animals discriminate paternal kin from non-kin and bias their social behavior accordingly is being debated. This study explores the relative importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
3
21
1
Order By: Relevance
“…In these primates, kin-biased affiliative interactions, often measured using grooming and proximity, are common. 36 These include interactions between close maternal relatives (mother-daughters, maternal-siblings) [37][38][39][40][41][42] and, to a lesser extent, paternal relatives [38][39][40][41] (Fig. 2).…”
Section: Friendship In Primates and Other Animalsmentioning
confidence: 99%
“…In these primates, kin-biased affiliative interactions, often measured using grooming and proximity, are common. 36 These include interactions between close maternal relatives (mother-daughters, maternal-siblings) [37][38][39][40][41][42] and, to a lesser extent, paternal relatives [38][39][40][41] (Fig. 2).…”
Section: Friendship In Primates and Other Animalsmentioning
confidence: 99%
“…Recent studies have also documented kin bias among paternally related cercopithecine females. Adult female baboons showed similar affiliative bias toward maternal and paternal half-sisters [Smith et al, 2003], whereas female rhesus macaques showed a stronger affiliative kin bias to maternal than to paternal half-sisters [Schülke et al, 2013;Widdig et al, 2001Widdig et al, , 2006. The strength of affiliation of paternal relatives may depend on whether there are strong bonds with maternal kin [Charpentier et al, 2012;Silk et al, 2006].…”
Section: Introductionmentioning
confidence: 96%
“…In almost all cercopithecines, females are philopatric and live together with their female kin for life. Close maternal kin commonly show high levels of affiliation [reviewed in Berman, 2011; more recent reports by Charpentier et al, 2012;Schülke et al, 2013;Johnson et al, 2014]. Recent studies have also documented kin bias among paternally related cercopithecine females.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have linked social position to home range (see Pinter-Wollman et al, 2013 for a review), social status (Sueur & Petit, 2008), age (Patriquin, Leonard, Broders, & Garroway, 2010), sex (Carter Seddon, Fr ere, Carter, & Goldizen 2013;Gilby & Wrangham, 2008), genetic relatedness (Archie, Moss, & Alberts, 2006;Carter, Seddon, Fr ere, Carter, & Goldizen, 2013;Schülke, Wenzel, & Ostner, 2013), the acquisition of social information (Aplin, Farine, Morand-Ferron, & Sheldon, 2012;Aplin et al, 2014;Claidiere, Messer, Hoppitt, & Whiten, 2013), disease status (Weber et al, 2013) and reproductive success (Wey et al, 2013). Additionally, there has been increasing recent interest in social network position as a personality trait or part of a wider behavioural syndrome (Krause, James, & Croft, 2010;Wilson, Krause, Dingemanse, & Krause, 2013).…”
mentioning
confidence: 99%